Uterine Artery Pseudoaneurysm after Cesarean Section Treated with Superselective Embolization: A Case Repor - Jullie Anne Chiste, Larissa Cavalli de Oliveira, Liziane Lorusso, Anna Luisa Aranha Nunes, João Vitor Bacarin (Advanced Ultrasound in Diagnosis and Therapy, 2022)
Uterine artery pseudoaneurysm is a rare complication associated with obstetric or gynecological procedures. We described a case report of a primigravid, underwent cesarean section who evolved with massive, intermittent vaginal bleeding requiring multiple blood transfusions. The diagnosis of uterine artery pseudoaneurysm was suspected on transvaginal Doppler ultrasound and confirmed on computed tomography angiography. Due to the patient's stability, age and undefined offspring, superselective uterine artery embolization was chosen for treatment and the procedure successfully performed.